(untitled) (Journal of the College of Basic Education, 2022)
Design and evaluation of a broadband and wide angle antireflection coating (AR) for solar cell can operate at incident angles of 00-700 and over a wavelength range of 400-1200 nm were studied in details in this paper. The antireflection system consists of two layers of MgF2 and TiO2 in the form: Air/ MgF2, TiO2/ Si. The target reflection spectrum at any incident angle must be minimum for whole range of wavelength (400-1200 nm). The designs are based on the optical thin film theory, with the aid of an optimization method. The results indicate that the AR coatings thicknesses that give minimum reflection are function of incident angles. Also the error in reflectance spectrum increased with the increase in incident angle. It is obvious that the thickness of MgF2 material is more influence by angle of light incident than TiO2 material thickness which is approximately a constant thickness.